Digital Privacy Crisis: Legal Protection of Social Media Users' Data in Indonesia's 2022 Law - Lihawa, Rahmad (Universitas Negeri Gorontalo, 2025)
This study analyzes the challenges in implementing Indonesia's Law Number 27 of 2022 on Personal Data Protection (PDP Law) and explores the roles of stakeholders in ensuring its effectiveness. The research identifies obstacles in the law's implementation and highlights how collaboration between electronic system organizers, the government, legal practitioners, and the public can improve personal data protection in the digital era. Using a qualitative approach with descriptive analysis, data is gathered from literature studies, legal documents, reports, articles, and interviews with legal professionals, regulators, and companies operating electronic systems. Content analysis is used to identify key issues related to the PDP Law’s implementation, challenges, and stakeholder roles. A comparative approach is also applied to evaluate how the PDP Law compares to other regulations, such as the EU’s GDPR. The findings indicate that while the PDP Law provides a solid legal framework, its implementation faces challenges, including limited resources at the Personal Data Protection Agency (BPDP), low public awareness, and inconsistencies between Indonesian policies and international platforms. Additionally, there are differing interpretations of personal data management policies between regulators and electronic system organizers. The study stresses the need for collaboration among stakeholders, increased legal education, and stricter supervision to ensure the law's effective implementation